Interim recommendations concerning the functioning of nursing homes (Central Board for Public Health) - Wimmers, M F (Tijdschrift voor gerontologie en geriatrie, 1982)
In june 1982 the Advisory Committee of the Central Board of Health presented its latest report on the functioning of nursing homes in the Netherlands. This publication is actually the Committee's fourth report in succession, the third report having been submitted in 1972. When seeking renewed advice, the Minister of Health and Environmental Control required an answer to eight very concrete questions, centering on the conception that the quality of life in nursing homes should be greatly improved without involving any additional expenditure. It is considered an asset of the Advisory Committee that their recommendations do not require the tapping of other financial sources. The fact, however, that no contribution was made to the improvement of the living conditions in nursing homes, the very question so urgently raised by the Minister, is looked upon as a great disadvantage. In brief, the latest report contains no new ideas! A repetition of the arguments quoted ten years ago can hardly have been the object the Minister had in mind, when seeking renewed advice. It goes without saying that a new report will have to be submitted on the qualitative functioning of nursing homes. Time presses! It will be necessary for a Committee of wise men to be appointed, willing to put forward innovating ideas and being able to defend them with enthusiasm.